The Effectiveness of Using Picture Series to Teach Reading Comprehension - Qonita Haqq Alqy; Mukminatus Zuhriyah (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
Reading is an activity carried out by someone to get information previously unknown to the reader, and picture series is an interesting media for students to understand reading texts by illustrating. This study aimed to know students' reading comprehension before and after using picture series and whether or not using picture series to teach reading comprehension was effective. This research was a pre-experimental study using one group pre-test and post-test design. This research used class X students of MA Terpadu Al-Munawaroh as the population. The sample was class X-A students, totaling 18 people who were selected through the purposive sampling method. The instrument used was a reading comprehension test, and the validity and reliability were tested first using SPSS 25. The results of this research indicated that post-test mean score was higher than the pre-test. Students find it easier to catch and summarize reading content with pictures and they can retell using their own language easily. So, it could be revealed that teaching reading using the picture series of students’ class X-A was effective. Then, it was highly recommended to use picture series for teachers or other researchers in listening or writing.